Longitudinal Vehicle Control based on Off-road Tire Model for Soft Soil Applications. Issue 10 (2021) - Vieira, David; Orjuela, Rodolfo; Spisser, Matthias; Basset, Michel
Abstract: Autonomous off-road vehicles such as tractors, military vehicles, construction and agricultural machinery require an important power traction to face off mobility issues on soft soils and rough terrains. This paper presents a powertrain controller developed using an adapted Burckhardt tire model based on a Bekker-Wong wheel-soil interaction model according to the plasticity theory and soil mechanics. A Gain Scheduling approach allows the vehicle to maintain the desired reference speed while avoiding the impact of ground conditions. Simulation results show vehicle mobility control through different types of soils.